MEMBANGUN PARADIGMA TAFSIR PREVENTIF DALAM STUDI ALQURAN KONTEMPORER - Ade Naelul Huda; Sabri bin mohamad; Muhammad Azizan Fitriana (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2026)
This study aims to construct a preventive tafsir paradigm in contemporary Qur’anic studies through an analysis of Qur’anic concepts oriented toward wiqāyah (protection and prevention). The study is motivated by the increasing complexity of contemporary social problems, such as sexual violence, moral degradation, bullying, family crises, corruption, social disintegration, and natural resource exploitation, which require approaches that are not only curative but also preventive. This research employs a qualitative library-based methodology using a thematic interpretation (tafsīr mawdū‘ī) approach. Primary data are derived from the Qur’an, while secondary sources include classical and contemporary tafsir works, literature on maqāṣid al-sharī‘ah, usūl al-fiqh, and previous studies related to preventive concepts in Islam. Data were analyzed through the identification, categorization, and synthesis of Qur’anic verses containing orientations of protection and prevention. The findings reveal that the preventive tafsir paradigm in the Qur’an is constructed through five principal concepts. First, at-taqwā, which refers to avoiding corruption from within oneself (self-avoidance). Second, lā taqrabū, which signifies avoiding pathways that lead to harm (avoidance of pathways). Third, al-ijtināb, which emphasizes avoiding sources of corruption (avoidance of harmful sources). Fourth, al-iṣlāḥ, which aims at preventing the spread and escalation of social harm (avoidance of social deterioration). Fifth, an-nahy ‘an al-munkar, which functions as the collective avoidance of social evil (collective avoidance of social evil). These five concepts form an interconnected system of protection designed to safeguard religion, life, intellect, morality, family, and social order. The study concludes that the Qur’an not only provides solutions to existing social problems but also establishes a comprehensive anticipatory and preventive system of protection. Theoretically, this research offers a new conceptual framework in the form of a preventive tafsir paradigm as a complement to existing approaches in contemporary Qur’anic studies, including social tafsir, maqāṣidī tafsir, and contextual tafsir.